Resistenza e resilienza in Cipriano di Cartagine e Gregorio di Nazianzo - Accorinti, Domenico (Vox Patrum, 2022)
As Clemens Sedmak and Małgorzata Bogaczyk-Vormayr point out in their introduction to Patristik und Resilienz (Berlin 2012), human resilience must be understood as the ability to change oneself in response to a crisis, and not to return to a starting point (Einleitung, 3). After an introductory part on the different meanings and aspects of resilience, this paper discusses some texts by Cyprian of Carthage (De mortalitate, Ad Demetrianum, De bono patientiae, De dominica oratione) and Gregory of Nazianzus (Or. 26, Ep. 223, 30-36, 92) that may be of some interest for the current discussion on resilience. Indeed, starting from the same eschatological perspective, both authors seem to share a dynamic notion of resilience, which is not a mere endurance of the adversity, but the ability to transform a negative situation into an existential resource.